Teoría y práctica de la Ley. Apuntes sobre tres juristas indianos - Cuena Boy, Francisco (Cuadernos de Historia del Derecho, 2007)
The legal system of Spanish colonies in America (the so-called “Derecho Indiano”) is characterized by its remarkable casuism. However, the statutory law always appeared as one of the essential elements of that legal system, as indispensable for the theoretical thought about law as for the practical performance of the rules. The purpose of this paper is to show this afore-mentioned value of the statutes through the doctrines and opinions of three “Indiano” jurists of the XVIth century: Fr. Miguel Agia, Diego de Avendaño and Alonso de la Peña Montenegro.